A Screening Picture Speech Identification Test for Nepali Speaking Children - Khanal, Kabi Raj; Dattatreya, T; Karna, Sureshwar Lal (Nepalese Journal of ENT Head and Neck Surgery, 2014)
DOI: http://dx.doi.org/10.3126/njenthns.v3i2.10157 Nepalese Journal of Head and Neck Surgery Vol.3(2) 2012: 15-16